Profit people and planet - Joshi, Havovi (Institutional Knowledge at Singapore Management University, 2019)
On behalf of the Editorial Board of Asian Management Insights, its authors and readers, I would like to thank our outgoing Editor-in-Chief, Dr Philip Zerrillo, who founded the magazine and invested signifi cant efforts to advance its profi le these past five years.